Agricultural trade and food security: Some thoughts about a continuous debate - Díaz-Bonilla, Eugenio (International Centre for Trade and Sustainable Development, 2013)
Summary report for the E15 Expert Group on Agriculture and Food Security. This paper is an input to the work of the “Expert Group on Agriculture, Trade and Food Security Challenges” as part of the E-15 Initiative of the International Center for Trade and Sustainable Development (ICTSD). The group on agriculture and trade is co-convened with the International Food and Agricultural Trade Policy Council (IPC).